Deconstructing the WISE nearby galaxy population - August, Tamlyn (Department of Astronomy, 2020)
This thesis aims to test the reliability of the Wide-Field Infrared Space Explorer (WISE) star formation indicators centred at 12 and 22 µm. To accomplish this, the total infrared (TIR) luminosity was used as a calibrator to understand the behaviour of the two indicators. Our sample consists of Spitzer galaxies from the SINGS and KINGFISH surveys, with a select few excluded. The TIR calibration also necessitates that most of our galaxies have FIR data from Herschel. The photometric analysis done on the raw WISE and Spitzer images of our galaxies is explained, including how the isophotes and background sky level were determined for each band/image. Once the reliability of the WISE indicators was established, new star formation rate relations were formulated. The new relations are comparable to previous relations in the literature, but improve on them in stellar mass-, metallicity-, and luminosity range. We also find that metallicity of the galaxies has minimal effect on our relations. In our comparison of emission from PAH molecules, the two bands in question, IRAC4 and W 3 are strongly correlated. This may suggest that the W3 band is dominated by emission from the 11.3 µm PAH molecule, or it might be an effect of the band overlap between IRAC4 and W3.